EFFECTS OF DIFFERENT KINDS OF FOOD ON THE GROWTH AND SURVIVAL RATE OF AD ULT TIGER TAIL SEAHORSE (HIPPOCAMPUS COMES , 1850) - Ky, Truong Si; Hoa, Ho Thi; Lu, Hoang Duc; Lang, Pham Vu (Vietnam Journal of Marine Science and Technology, 2009)
This study examined the effects on the growth and survival rate of culturedtiger tail seahorse (Hippocampus comes) fed on Mysis and Aceres and a com bination of these foods. The results show that there are no significant difference in length and weight between treatments of Mysis and Acetes, but length of seahorsefed on Acetes and Mysis combinarion is higher than that of another tremments (P < 0.05).Survival rate of seahorse for all treatments is higher than 97%. In conclusion, this in vestigation has demonstrared effective use of frozen Mysis and Aceres for seahorse aquaculture. Mysis and Acetes are available in Vietnamese seawaters, but rhey seasonally occur, so should buy and keep them in frozen condition and using for seahorse culture whole year. These foods can be used as an alternative to live enriched Artemia, that fed seahorse in the past.